Analysing the environmental Kuznets curve for CO2 emissions in China using segmented equations and partial least squares. (2015) - Gao, Qian; Meng, Ming; Wen, Lei; Niu, Dongxiao
This study investigates the dynamic relationship between economic growth and CO2 emissions in China from 1979 to 2010. We propose a segmented equation for the environmental Kuznets curve (EKC). The partial least squares method is used to estimate the equation parameters. The conclusions drawn are as follows: 1) China's CO2 emissions are still in the first stage of the EKC. A significant increase in income per capita is needed for China's CO2 emissions per capita to reach its peak point in the inverted U-shaped EKC; 2) the ideal equation used to simulate the relationship between China's income per capita and CO2 emissions per capita after 2010 is In(Ct ) = −13.3568 + 3.1708In(It ) − 0.1608(In(It )) 2 . This equation can help China's government set its ideal CO2 control target at a specific income per capita, at least until the income per capita reaches RMB 19, 137.2; 3) China's CO2 emissions per capita will peak some time between 2026 and 2027. After 2027, China's CO2 emissions per capita will decrease as income per capita increases.